Shared decision making and decisional conflict in the Management of Vestibular Schwannoma: a prospective cohort study - M. Elise Graham; Brian D. Westerberg; Jane Lea; Paul Hong; Simon Walling; David P. Morris; Andrea L. O. Hebb; Rochelle Galleto; Emily Papsin; Maeve Mulroy; Hannah Foggin; Manohar Bance (Journal of Otolaryngology - Head and Neck Surgery)
Abstract Background Patients with vestibular schwannomas (VS) are faced with complex management decisions. Watchful waiting, surgical resection, and radiation are all viable options with associated risks and benefits. We sought to determine if patients with VS experience decisional conflict when deciding between surgery or non-surgical management, and factors influencing the degree of decisional conflict. Methods A prospective cohort study in two tertiary ambulatory skull-base clinics was performed. Patients with newly diagnosed or newly growing vestibular schwannomas were recruited. Patients were given a demographic form and the decisional conflict scale (DCS), a validated measure to assess the degree of uncertainty when making medical decisions. The degree of shared decision making (SDM) experienced by the patient and physician were assessed via the SDM-Q-10 and SDM-Q-Doc questionnaires, respectively. Non-parametric statistics were used. Questionnaires and demographic information were correlated with DCS using Spearman correlation coefficient and Mann-Whitney U. Logistic regression was performed to determine factors independently associated with DCS scores. Results Seventy-seven patients participated (55% female, aged 37–81 years); VS ranged in size from 2 mm–50 mm. Significant decisional conflict (DCS score 25 or greater) was experienced by 17 (22%) patients. Patients reported an average SDM-Q-10 score of 86, indicating highly perceived level of SDM. Physician and patient SDM scores were weakly correlated (p = 0.045, Spearman correlation coefficient 0.234). DCS scores were significantly negatively correlated with a decision to pursue surgery, presence of a trainee, and higher SDM-Q-10 score. DCS was higher with female gender. Using logistic regression, the SDM-Q-10 score was the only variable associated with significantly reduced DCS. Conclusions About one fifth of patients deciding how to manage their vestibular schwannoma experienced a significant degree of decisional conflict. Involving the patients in the process through shared decision-making significantly reduced the degree of uncertainty patients experienced.